Franchise Protection Law to Secure Rights and Obligations in Joint Business - Christian, Benedict Philip (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
Franchise business (franchise) is a business system that is currently favored by many people. From the franchise system, doing business becomes easier, because franchising is the right of each entrepreneur or business entity to market goods or services that are proven by the running of a "successful" business by being used by other parties based on a franchise agreement. Here the author wants the parties to pay close attention to the information discussed in connection with the franchise agreement. The parties are responsible for all the contents of this information and prevent its dissemination or leakage to third parties or the public, because that is why it is important to include a confidentiality clause in the franchise agreement so that the information obtained is safeguarded and does not result in loss to the owner due to information leakage. In the franchise business, the law of protection for every profit is needed as regulated in the Government Regulation of the Republic of Indonesia Number 42 of 2007 which regulates Franchising and is further regulated by the Regulation of the Minister of Trade of the Republic of Indonesia Number 53/M-DAG/PER/8/2012 concerning the Implementation of Franchising